Pemahaman Perpajakan, Kepercayaan Kepada Pemerintah, Kualitas Pelayanan dan Kepatuhan Wajib Pajak Kendaraan Bermotor - Darmawan, I Wayan; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 32 No 7 (2022), 2022)
This study aims to obtain empirical evidence related to the effect of understanding taxation, trust in the government, and service quality on motor vehicle taxpayer compliance. This research was conducted at the Joint Office of SAMSAT Klungkung with the number of samples used determined by the slovin formula so that 100 taxpayers were obtained. The method of determining the sample uses a non-probability sampling technique with accidental sampling. Data was collected by giving questionnaires to selected respondents and analyzed using multiple linear regression analysis techniques. Based on the results of the analysis, it can be concluded that trust in the government has a significant positive effect on motor vehicle taxpayer compliance. While the understanding of taxation and service quality does not affect the compliance of motorized vehicle taxpayers. Keywords: Understanding Taxation; Trust in Government; Quality of Service; Taxpayer Compliance.